Lesional Infiltration of Eosinophils, Basophils, and M2 Macrophages Expressing Eotaxin-1 and Eotaxin-3 in Granuloma Faciale, but not in Erythema Elevatum Diutinum - Nozomi Akai; Takashi Hashimoto; Manami Okuzawa; Satoshi Okuno; Takahiro Satoh (Acta Dermato-Venereologica, 2024)
Abstract is missing (Short communication)